2012
DOI: 10.1177/159101991201800105
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Neurological Deficit from Iodinated Contrast Encephalopathy following Intracranial Aneurysm Coiling

Abstract: Neurotoxicity from iodinated contrast agents is a known but rare complication of angiography and neurovascular intervention. Neurotoxicity results from contrast penetrating the blood-brain barrier with resultant cerebral oedema and altered neuronal excitability. Clinical effects include encephalopathy, seizures, cortical blindness and focal neurological deficits. Contrast induced encephalopathy is extensively reported as a transient and reversible phenomenon. We describe a patient with a persistent mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
152
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(154 citation statements)
references
References 53 publications
0
152
2
Order By: Relevance
“…Since symptoms may persist or appear in the subacute period, although very rarely, 16,17) attention to contrast-induced encephalopathy is considered necessary as a complication of intracranial endovascular treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Since symptoms may persist or appear in the subacute period, although very rarely, 16,17) attention to contrast-induced encephalopathy is considered necessary as a complication of intracranial endovascular treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms by which contrast agent causes neurotoxicity should be discussed (7). Under normal conditions, intravenous contrast material does not diffuse in the BBB (7). But when BBB is disrupted, over dose contrast agent is applied or contrast agent is applied intra-arterially, transfer of contrast material increases (7).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it should be kept in mind that contrast matters used in various ways (intravenous, intra-arterial, intrathecal) in different radiological imaging methods can result in neurotoxicity. Mechanisms by which contrast agent causes neurotoxicity should be discussed (7). Under normal conditions, intravenous contrast material does not diffuse in the BBB (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 There is conflicting evidence regarding increased neurotoxicity once the IRCM has crossed the BBB in animals and humans. 17,[25][26][27][28][29] Heinrich et al 30 compared the direct cytotoxic effects of dimeric iso-osmolar and monomeric isoosmolar IRCM on renal tubular cells in vitro and found that dimeric IRCM have stronger direct cytotoxic effects, postulating a mechanism independent from osmolarity. 30 Molecular chemotoxicity, related to the chemical structure of the molecule, decreases as the number of carboxyl groups decreases and the number of hydroxyl groups increases.…”
Section: Discussionmentioning
confidence: 99%